Histopathological pulp response of dog's teeth capped with biosealer and biodentine: An in vivo study - Inas M Al-Sherbiny; Ashraf M Abu-Seida; Mona H Farid; Inas T Motawea; Hagar A Bastawy (Wolters Kluwer Medknow Publications, 2020)
Introduction: The aim of this study was to evaluate the pulpal response after pulp capping using either biodentine (BD) or tech biosealer capping (TBC) in the dog model. Materials and Methods: Class V cavities were carried out on 45 teeth in three mongrel dogs. The dental pulp was exposed in 30 teeth (2 experimental groups) and left unexposed in 15 teeth (control group). The cavities of the experimental groups were capped with either BD (n = 15 teeth) or TBC (n = 15 teeth). All cavities in the experimental and control groups were restored with resin-modified glass ionomer. Dentin bridge formation, architecture of the odontoblastic layers, and signs of inflammation were assessed after 1, 2, and 3 months using the computer image analyzer. Results: The BD group exhibited a thick newly formed reparative dentin bridge completely closing the exposure site with cell inclusions and mineralization, variable numbers of odontoblast-like cells, preserved pulp tissue, marked numerous collagen fibers, and blood vessels. While the TBC group exhibited an incomplete newly formed reparative dentin bridge with tunnel defect, vacuolated odontoblasts, complete pulp degeneration with multiple edematous spaces, hyperemic blood vessels, extravasated red blood cells, multiple calcified structures scattered just beneath the dentin bridge and through the pulp tissue, and newly ill-defined odontoblasts. Conclusion: For pulp capping, BD has a better dentin bridge formation and pulp preservation than TBC in the dog model.